Animal morality - around Wild Justice by Marc Bekoff and Jessica Pierce. Preliminary analyses - Strzyżyński, Przemysław (Filozofia Chrześcijańska, 2023)
The article analyzes the concept of morality proposed by Bekoff and Pierce in the context of animal morality in the book Wild Justice. Differences are shown in comparison to the understanding of morality in the human context. On this basis, it is suggested to use the name (proto)morality for animal behavior similar to the moral behavior of humans. Part of the article analyzes the concept of empathy used in the context of animals. The article also argues to use the third type of moral status of moral (proto)subjectivity.